An Exponential Rarefaction Result for Sub-Gaussian Real Algebraic Maximal Curves - Bayraktar, Turgay; Karaca, Emel (Comptes Rendus. Mathématique)
We prove that maximal real algebraic curves associated with sub-Gaussian random real holomorphic sections of a smoothly curved ample line bundle are exponentially rare. This generalizes the result of Gayet and Welschinger [13] proved in the Gaussian case for positively curved real holomorphic line bundles.